Efficient and broadband subwavelength grating coupler for 3.7 μm mid-infrared silicon photonics integration - Chen, Nan (2019)
A grating coupler is an essential building block for compact and flexible photonics integration. In order to meet the increasing demand of mid-infrared (MIR) integrated photonics for sensitive chemical/gas sensing, we report a silicon-on-insulator (SOI) based MIR subwavelength grating coupler (SWGC) operating in the 3.7 μm wavelength range. We provide the design guidelines of a uniform and apodized SWGC, followed by numerical simulations for design verification. We experimentally demonstrate both types of SWGC. The apodized SWGC enables high coupling efficiency of −6.477 dB/facet with 3 dB bandwidth of 199 nm, whereas the uniform SWGC shows larger 3dB bandwidth of 263.5 nm but slightly lower coupling efficiency of −7.371 dB/facet.